Comparative Cyto-Histological Genetic Profile in a Series of Differentiated Thyroid Carcinomas - Matos, Maria de Lurdes (2024)
Funding Information: This research received funding for SC, in the framework of a Ph.D. grant (SFRH/BD/147650/2019) supported by Portuguese funds through Fundação para a Ciência e a Tecnologia (FCT). This study is part of the project “Institute for Research and Innovation in Health Sciences” (UID/BIM/04293/2019) and the project “The Porto Comprehensive Cancer Center” ref. NORTE-01-0145-FEDER-072678—Consórcio PORTO.CCC—Porto. Comprehensive Cancer Center Raquel Seruca. Publisher Copyright: © 2024 by the authors.